Transcriptome analysis revealed potential genes involved in thermogenesis in muscle tissue in cold-exposed lambs - Ji, Kaixi; Jiao, Dan; Yang, Guo; Degen, Abraham Allan; Zhou, Jianwei; Liu, Hu; Wang, Wenqiang; Cong, Haitao (Frontiers in Genetics, 2022)
Cold tolerance is an important trait for sheep raised at high altitudes. Muscle tissue, comprising 30 to 40% of the total body mass, produces heat during cold exposure. However, little is known about the genetic mechanisms in these tissues in the regulation of thermogenesis in lambs. We examined genes in skeletal muscle tissue in a cold-adapted sheep breed, Altay, and a cold-intolerant sheep breed, Hu, when exposed to low air temperature. Three ewe-lambs of each breed were maintained at -5℃ and three ewe-lambs of each breed were maintained at 20℃. After cold exposure for 25 days, the longissimus dorsi of each lamb was collected, then transcriptome profiles were sequenced and further analyzed. The results of RNA-seq showed that the average reads among the four groups were 11.0 Gbase. The genome mapping rate averaged 88.1% and the gene mapping rate averaged 82.5%. The analysis of differential expressed genes (DEGs) indicated that PPAR, cAMP, and calcium signaling pathways and muscle contraction in muscle tissue were linked to thermogenesis in cold-exposed lambs. Furthermore, PCK1 (phosphoenolpyruvate carboxykinase1) increased gluconeogenesis in cold-exposed Altay lambs, and APOA2 (apolipoprotein A2), APOC3 (apolipoprotein C3), LPL (lipoprotein lipase), and FABP4 (fatty acid binding protein 4, adipocyte) were involved in the intake and transport of free fatty acids. In Hu sheep, cAMP biosynthesis from ATP hydrolysis was mediated by ADCY10 (adenylate cyclase) and ADORA2a (adenosine A2a receptor). Skeletal muscle contraction was regulated by MYL2 (myosin light chain 2). In conclusion, cold exposure altered the expression level of genes involved in heat production in muscle tissue. Some potential mechanisms were revealed, including calcium ion transportation in the calcium signaling pathway, glucose and fatty acid metabolism in the PPAR signaling pathway, and cAMP biosynthesis in the cAMP signaling pathway. This study implied that this tissue plays an important role in thermoregulation in lambs.